VARIASI BAHASA PEDAGANG SEBAGAI SALAH SATU BENTUK KERAGAMAN BAHASA: (Kajian Deskriptif Analitis terhadap Penggunaan Bahasa Pedagang Pasar Baru Kabupaten Indramayu Jawa Barat) - Logita, Embang; Juidah, Imas (Universitas Wiralodra, 2022)
With the existence of Indonesia as the national language and accompanied by various regional languages, the Indonesia people have a very rich variaty of languages. So we need to take care of this form so that it is not eroded by the times. The trader of pasar baru Indramayu are part of the Indramayu community who speak Javanese-Sundanese language in communicating because geographically it is on the border of Sunda and Java, so that majority of the population is mixed between Sundanese and Javanese. Likewise, on of the language variations that exist in the Pasar Baru Indramayu merchants communtity which has diversity, where based on research it out that the Pasar Baru Indramayu merchants community that we know in general in their language use javanese but it turns out that communicating there are other regional languages, namely Sundanese and Indonesian according to the context they are spoken to. Based on the result of the study, that in the speech of traders, especially those of Pasar baru traders, there are language variations. Language variations that occur in the speech of these traders generally ocuur because of the language user factor itself and the factor of its use. In terms of language users, language variations occur due to geographical factor that cause regional variations (dialects). In additions, in terms of users, language variations also occur because of the influence of the interlocuter. In terms of language use, language variation in terms of the topic of the problem, generally trades always say quantiti (amount).